Analysis of distillation unit by using the meihod of flickernoise spectroscopy - Novakovska, Natalia; Kyshenko, Vasil (My University, 2015)
To establish the fundamental changes in the behavior of the distillation process, to prevent the occurrence of critical situations the proposed method of flicker-noise spectroscopy. The parameters of the method by studying the specific conditions of the object on the time-series operation bragorektifikatsionnry installation distillery.
Keywords: production of alcohol; rectification; forecasting; flicker-noise spectroscopy; виробництво спирту; ректифікація; прогнозування; флікер- шумова спектроскопія; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка